Cranial approach to the left hepatic vein in laparoscopic anatomic liver resections of segment 2 and segment 3. (December 2020) - Monden, Kazuteru; Sadamori, Hiroshi; Hioki, Masayoshi; Takakura, Norihisa
Abstract: Background: The cranial approach allows easy identification of the major hepatic vein Ome et al. (2020), Honda et al. (2013), Xiao et al. (2016) and Kim (2019) [1–4 ] and avoids split injury of the hepatic veins (HV) by exposing the HV from the root to the periphery (Honda et al., 2013) [2 ]. We present the cranial approach to laparoscopic anatomic liver resections of segment 2 (S2) and segment 3 (S3) in two cases of hepatocellular carcinoma (HCC). Methods: [Laparoscopic segmentectomy 2]After dissection of the S2 Glissonean pedicle, parenchymal transection was initiated to expose the dorsal aspect of the root of the left hepatic vein via parenchymal transection using a cranial approach. The cavitron ultrasonic surgical aspirator (CUSA) was used from the root side towards the peripheral side. The liver parenchymal dissection was completed by dissecting between the demarcation line and the left hepatic vein. [Laparoscopic segmentectomy 3]The liver transection was initiated along the falciform ligament. After the S3 Glissonean pedicle was temporally clamped, the ventral aspect of the root of the left hepatic vein was exposed peripherally. The parenchymal dissection process was completed with the S3 Glissonean pedicle dissection. Results: S2: The operation time was 191 min, the estimated blood loss was 5 ml, and the patient was discharged on postoperative day 5 with no complications. S3: The total operation time was 215 min, the estimated blood loss was 50 ml, and the patient was discharged on postoperative day 9 with no complications. Conclusion: The cranial approach is a safe method for laparoscopic anatomic liver resections of segments 2 and 3. Highlights: Laparoscopic segmentectomies 2 and 3 are performed for hepatocellular carcinoma. Laparoscopic segmentectomies 2 and 3 using a cranial approach can preserve remnant liver function. Exposure of the major hepatic vein, a dissection landmark, is essential. The cranial approach safely exposes the major hepatic vein from the root.